2021
DOI: 10.1016/j.intimp.2021.108145
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing interstitial lung disease in patients with coronavirus disease 2019: A meta-analysis

Abstract: Background The impact of pre-existing interstitial lung disease (ILD) on the severity and mortality of COVID-19 remains largely unknown. The purpose of this meta-analysis was to investigate the prevalence of ILD among patients with COVID-19 and figure out the relationship between ILD and the poor clinical outcomes of COVID-19. Methods A systematic literature search was conducted in the PubMed, EMBASE, Web of Science and MedRxiv Database from 1 January 2020 to 26 May 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…The spike protein of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), responsible for causing the coronavirus disease-2019 (COVID- 19), mediates attachment of the virus to host cell-surface receptor and fusion between virus and cell membrane [1]. The spike protein consists of two subunits: S1 (containing the angiotensin converting enzyme 2 (ACE2) receptor-binding domain) and S2 (responsible for the fusion process) [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spike protein of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), responsible for causing the coronavirus disease-2019 (COVID- 19), mediates attachment of the virus to host cell-surface receptor and fusion between virus and cell membrane [1]. The spike protein consists of two subunits: S1 (containing the angiotensin converting enzyme 2 (ACE2) receptor-binding domain) and S2 (responsible for the fusion process) [2].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of IPF is excessive extracellular matrix deposition within the lung interstitium, leading to the destruction of normal parenchymal structure and a corresponding loss of pulmonary function. The meta-analysis study performed by Ouyang et al [19] that included 135,263 COVID-19 patients from 15 cohorts concluded that pre-existing interstitial lung disease is associated with higher severity and mortality of COVID-19. The most common short-term post-COVID-19 fibrotic patterns included ground glass opacities and linear bands, bronchiectasis/bronchiolectasis, and loss of volume in the bilateral posterior lung segments.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in a meta-analysis that included 15 studies (135,263 COVID-19 patients), the rate of ICU admission and mortality was significantly higher in patients with ILD than those without, indicating that ILD may be a risk factor for poor clinical outcomes of patients with COVID-19. 9 …”
Section: Do Patients With Pulmonary Fibrosis Have More Severe Lung Di...mentioning
confidence: 99%
“…Previous individual studies on the association between pre-existing interstitial lung disease and the risk for severity and mortality of patients with coronavirus disease 2019 (COVID-19) yielded inconsistent results [1] , [2] , [3] , [4] . Recently, Ouyang et al have performed a meta-analysis to address the impact of pre-existing interstitial lung disease on the severity and mortality among COVID-19 patients in the journal of International Immunopharmacology [5] . Their data suggested that pre-existing interstitial lung disease was associated with higher risk for severity and mortality of COVID-19 patients.…”
mentioning
confidence: 99%
“…However, the number of included studies (3 articles) and the sample sizes (8691 participants) were relatively small, and the stability of the overall results was not evaluated, moreover, the pooled effect size was calculated on the basis of un-adjusted effect estimates in Ouyang et al’s study [5] . As the authors mentioned, sex, age and certain comorbidities were known risk factors for severe COVID-19 and poor prognosis [5] , which indicates that these factors might confound the association between interstitial lung disease and COVID-19 severity and mortality. Taken together, we performed this updated meta-analysis on the basis of risk factors-adjusted effect estimates to clarify the association between interstitial lung disease and COVID-19 severity and mortality.…”
mentioning
confidence: 99%